2016
DOI: 10.1080/14606925.2016.1261504
|View full text |Cite
|
Sign up to set email alerts
|

Making “Making” Critical: How Sustainability is Constituted in Fab Lab Ideology

Abstract: Fab Labs, fabrication laboratories, are shared workshops where citizens can access digital fabrication equipment to design and make their own objects. They are proliferating rapidly and represent an alternative to mass production and consumption, an ideology whose environmental and social benefits their "makers" like to espouse. A longitudinal ethnographic study in a Fab Lab in a European design school examined the Lab's ideology building, how ideals were enacted and where compromises were visible. Environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 19 publications
(18 reference statements)
0
54
0
4
Order By: Relevance
“…fabrication laboratories) and makerspaces are alternative sites of production, set up by and for participants to use tools, equipment and facilities in order to design and produce their own artefacts. They offer means of personal fabrication in a social and collaborative set-up (Kohtala, 2016). Fab Labs are considered the most organized type of such sites, as they have a rather clear identity, held together by an international network (www.fablabs.io) fostering also production innovation and closer collaboration with business-partners.…”
Section: Alternative/diverse Fashion Practices Of Exchange and Value mentioning
confidence: 99%
See 1 more Smart Citation
“…fabrication laboratories) and makerspaces are alternative sites of production, set up by and for participants to use tools, equipment and facilities in order to design and produce their own artefacts. They offer means of personal fabrication in a social and collaborative set-up (Kohtala, 2016). Fab Labs are considered the most organized type of such sites, as they have a rather clear identity, held together by an international network (www.fablabs.io) fostering also production innovation and closer collaboration with business-partners.…”
Section: Alternative/diverse Fashion Practices Of Exchange and Value mentioning
confidence: 99%
“…Fab Labs are considered the most organized type of such sites, as they have a rather clear identity, held together by an international network (www.fablabs.io) fostering also production innovation and closer collaboration with business-partners. Makerspaces, in comparison, refer to any kind of collaborative workshop space (Kohtala, 2016), not necessarily emphasizing technology and innovation. Henceforth, the term makerspace is preferred in this article, as it implies the possibility for a more diversified program of making activities.…”
Section: Alternative/diverse Fashion Practices Of Exchange and Value mentioning
confidence: 99%
“…Osunyomi et al (2016a) observed a lack of research according to the sharing of information and the culture of global co-creation. Further in-depth questions arise about people's attitudes and their basic convictions (see, according to sustainability aspects, Kohtala, 2017;Fleischmann, Hielscher & Merritt, 2016). How do FabLab representatives themselves reflect the maker movement, what hinders them, what are their strengths?…”
Section: Fablabs and Makerspacesmentioning
confidence: 99%
“…In these environments, participants are expected to use these devices independently, encouraging peer learning and knowledge sharing, providing dynamic interactions for experimentation, education, research, and production among participants (Kohtala, 2017). Makerspaces are becoming increasingly popular features of Universities and other educational institutions, and the idea has even extended out into cities, with Makerspaces open to the public (Farritor, 2017).…”
Section: Introductionmentioning
confidence: 99%